TINJAUAN HUKUM ISLAM TERHADAP PERMOHONAN DISPENSASI NIKAH PADA PENGADILAN AGAMA PALOPO - Pasondong, Udin; Arafat Yusmad, H. Muammar; Beddu, Rahmawati (MADDIKA : Journal of Islamic Family Law, 2023)
The abstract contains a brief description of the research problem and objectives, methods used, and research results. It is written in two languages, English and Bahasa Indonesia. Key words need to be included to describe the domain of the problem under study and the main terms underlying the implementation of the research. Key words can be single words or a combination of words. Marriage dispensation is an exception to the rules or laws given to the applicant to enter into marriage. In this study the authors discuss the determination of a marriage dispensation application in civil case Number: 45/Pdt.P/2022/Pa.Plp. The problem examined is the basis for the judge's consideration in granting the application for marriage dispensation in civil case Number: 45/Pdt.P/2022/PA.Plp; and How is the review of Islamic law on the application for marriage dispensation in civil case Number: 45/Pdt.P/2022/Pa.Plp. This research is normative research. Where this research will refer to existing literature studies or secondary data used. The method of analyzing data material uses a qualitative method that is presented prescriptively. The results of this study indicate that the basis for the judge's consideration in granting the marriage dispensation application is the existence of urgent reasons. The judge's legal consideration in granting marriage dispensation is article 7 paragraph 2 of Law No.1 of 1974 concerning marriage, in the event of a deviation from the age limit for marriage, you can request dispensation from the Court or other officials appointed by both parents of the male and female parties. The judge's consideration outside the law uses the concept of mashlahah mursalah because the provisions of age limitation and marriage dispensation are not explained in the nash, but the content of the maslahat is in line with the actions of shara' which want to realize the benefit of the applicant (both prospective brides and their families) because there is an urgent matter, namely pregnancy first. Then in terms of adjudicating children related to marriage dispensation based on Supreme Court Regulation number 5 of 2019 concerning Guidelines for adjudicating applications for marriage dispensation.